Three consecutive generations of nephridia occur during development of Platynereis dumerilii (Annelida, Polychaeta) - Hasse, Christian; Tessmar-Raible, Kristin; Arendt, Detlev (Developmental dynamics, 2010)
Molecular data for nephridial development in polychaetes are not available yet. The scope of our work was to establish a reference system for future investigations using two markers for nephridial development: β-tubulin as marker for cilia and alkaline phosphatase (AP) activity for secretory epithelia. The markers identified, unexpectedly, three consecutively forming generations of nephridia: (1) a transitory unciliated, but AP-positive head kidney, (2) a transitory larval nephridium, which undergoes a morphological transition from a protonephridium to a funnelled nephridium concomitant with the development of the coelomic cavity and finally, (3) the serially arranged metanephridia. The spatial arrangement of larval and definitive nephridia, revealed an up to now unknown developmental boundary between the synchronously forming larval and the serially proliferating definitive segments. Development of three consecutive sets of nephridia with different morphology and biochemical properties was unexpected and reveals an interesting multistep process in the development of excretory structures in Platynereis. Developmental Dynamics 239:1967-1976, 2010. © 2010 Wiley-Liss, Inc.